Genetic divergence and speciation within Ziziphora capitata (Lamiaceae): Molecular and micromorphological evidences (Biodiversitas Journal of Biological Diversity, 2018)
Tabaripour R, Sheidai M, Talebi SM, Noormohammadi Z. 2018. Genetic divergence and speciation within Ziziphora capitata (Lamiaceae): Molecular and micromorphological evidences. Biodiversitas 19: 747-755. Ziziphora capitata is a member of the Mint family (Lamiaceae) that naturally grows in various regions. Different subspecies have been reported for this species, from which two are recorded from Iran: Z. capitata subsp. capitata, and Z. capitata subsp. orientalis. In the present study, morphological, palynological and molecular (ISSR and cp-DNA) data were used to reveal speciation within this species and reconsider taxonomic rank of its presumed subspecies. The obtained results revealed a great difference between two presumed subsp. of Z. capitata. These taxa differed in morphological, palynological and molecular characteristics. Statistical and bioinformatics tests revealed significant genomic difference between them and phylogenetic analyses showed that they have a close affinity to some other Ziziphora species (out-groups used), then to each other. Bayesian and maximum parsimony phylogenetic trees differentiated the presumed sub-species of Z. capitata. Moreover, K-Means clustering and Bayesian analysis of genetic groups by Evanno test (optimal k) supported the presence of two distinct genetic groups within Z. capitata. This approach objectively defines a threshold separating intraspecific population substructure from interspecific divergence, which is the general aim of species delimitation studies. Therefore, the present study provides enough evidence for introducing two separate species within Z. capitata based on the traditional taxonomy as well as combination of molecular and micro-morphological data.
Keywords: Bayesian tree; genetic distance; multiple approaches; species delimitation; Ziziphora